2015
DOI: 10.1177/0363546515574063
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical and Radiologic Evaluation of Patellofemoral Matrix-Induced Autologous Chondrocyte Implantation

Abstract: These results demonstrate that MACI provides improved clinical and radiologic outcomes to 24 months in patients undergoing treatment specifically for articular cartilage defects on the patella or trochlea, with and without concurrent realignment of the extensor mechanism if required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 48 publications
2
58
0
Order By: Relevance
“…In patients with focal III and IV degrees chondral defects, two studies have reported good clinical results after ACI 66,67. In both of these studies, a tibial tubercle transfer and lateral release was used to treat patients with patellofemoral malalignment 66,67.…”
Section: Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with focal III and IV degrees chondral defects, two studies have reported good clinical results after ACI 66,67. In both of these studies, a tibial tubercle transfer and lateral release was used to treat patients with patellofemoral malalignment 66,67.…”
Section: Therapymentioning
confidence: 99%
“…In both of these studies, a tibial tubercle transfer and lateral release was used to treat patients with patellofemoral malalignment 66,67. In a long-term follow-up study, ACI in combination with anteromedialization of the tibial tuberosity resulted in significant amelioration of symptoms and improvement in function with a low incidence of adverse events in patients with isolated, symptomatic, patellar chondral defects after a mean follow-up period of more than 7 years 68.…”
Section: Therapymentioning
confidence: 99%
“…The main indications for cartilage restoration are Outerbridge or International Cartilage Repair Society grade III or IV focal chondral or osteochondral defects of the loadbearing articular surface of the patellofemoral joint in patients with symptomatic knee pain in whom a sufficient trial of nonsurgical treatment has been unsuccessful. 1,3,4,6,7,10,12,15 General contraindications to cartilage restoration include osteoarthritis of the patellofemoral joint, inflammatory disease, medical contraindications, lower grade lesions, and patient inability to comply with postoperative rehabilitation protocols. 8 Additionally, outcomes may be better after management of unipolar lesions and contained lesions than after management of bipolar lesions and uncontained lesions.…”
Section: Indicationsmentioning
confidence: 99%
“…1,[7][8][9][10][11] Untreated chondral lesions may be a contributing factor in activity-limiting anterior knee pain. [4][5][6][7][8]10,[12][13][14] The main goal in managing patellar and trochlear chondral injuries is to restore cartilage surface congruity with sufficient biomechanical properties to alleviate symptoms, facilitate the return to previous level of activity, and improve quality of life. 5…”
mentioning
confidence: 99%
“…First generation of ACI used a porcine periosteal cover (ACI-P) which was replaced by a collagen type I/III cover in the second generation ACI-C both of which were secured with sutures; the collagen cover was proven to have lower instances of post-operative hypertrophy compared to periosteal covers [69,70]. Third generation of cell-based regenerative therapy for treatment of full-thickness cartilage defects is referred to as maxtrix-induced autoloug chondrocyte implantation (MACI) which adapted the second generation collage type I/III membrane into a bilayer membrane "seeded" with autologous chondrocytes and secured with fibrin glue [69][70][71][72][73][74]. MACI is a two-stage procedure including harvesting of chondrocytes for graft preparation then transplant/implantation of chondrocyte matrix graft approximately 4-6 weeks later.…”
Section: Autologous Chondrocyte Implantationmentioning
confidence: 99%